The Process of Symptoms and Coping Strategies Experienced in the Prodromal Schizophrenia: A Grounded Theory - Cheng, Chieh (ProQuest Dissertations & Theses, 2017)
Background: Schizophrenia is a debilitating disorder. Current research emphasizes changing the disease trajectory by prospectively identifying subjects at high risk based on the characteristics shown during the prodromal stage, which is the stage preceding the full-blown psychosis. However, the process of recognizing the prodromal stage remains unclear. Its non-specific features raise concerns about misdiagnosis, which stigmatizes patients who test false positive for being at risk of developing schizophrenia, resulting in a longer duration of untreated psychosis. Objectives: The purpose of the dissertation is to demonstrate a theoretical explanation of the prodromal schizophrenia process by describing patients’ symptoms, thoughts, feelings and coping strategies. Participants: Twenty-five adults with schizophrenia in Taiwan were interviewed. A total of 40 interviews were conducted at a medical center, two community settings, and one day care unit. Selection criteria included adults who were diagnosed with schizophrenia by DSM-IV diagnosis within the previous 5 years and who were in stable mental health status. Methods: Individual semi-structured interview questions were asked to explore meanings, role shifts, and proximate and ultimate causes. The Grounded Theory method was selected because it is used to explain the disease progression process during the prodromal stage. Constant comparison analysis, memo writing, member checking, and theoretical sampling were adopted. Results: Two coders analyzed the data. Inter-coder agreement was 95%. Participants’ age ranged from 20–40 years with a mean of 27.12 years old. The length of illness ranged from months to 5 years with a mean of 2.88 years. There was equal sex representation of patients (48% female; 52% male). Comparison of these categories led to their being consolidated into a core theoretical explanation in which the prodromal process is described as ranging from manageable to uncontrollable. Four categories emerged from the analysis: (1) something is wrong, (2) boiling up, (3) breaking point, and (4) losing control. Symptoms were either specific to each category or continuous across categories. Symptom severity increased with progression through the process. Before “losing control”, there are three corresponding coping strategies within each category: (1) making less, (2) trying to find former self, and (3) control taken away by others. Conclusions: This study provided a theoretical explanation using four stages with specific symptom manifestations for each. This study is the initial step in directing attention and increasing awareness toward early identification of warning signs that occur before full-blown psychosis.